Nutritional challenges in microgravity environments: A view of alimentation in space (Research, Society and Development, 2025)
The first human spaceflight took place in April 1961, when Soviet astronaut Yuri Gagarin orbited the Earth. Since then, scientists have sought to improve technologies to explore space and have been developing means of making these trips longer and longer. In order for these expeditions to be safe, detailed studies on the diet, physiology, and nutrition of astronauts are necessary. This study aimed to verify the diet of astronauts in space and its implications, analyze the impacts of microgravity on the nutritional status of astronauts during space missions, analyze possible changes in the digestive system of astronauts, and identify space factors that influence the taste of astronauts. In addition, priority was given to articles published in the last 10 years to ensure that the data were up-to-date, except in cases of studies considered fundamental to the subject. The results analyzed indicate that in order to reduce the adverse effects of microgravity, such as depletion of muscle mass and bone mass, changes in the immune system, cardiovascular dysfunctions, and eye changes, adequate and specific nutrition is necessary for this population. Thus, high-protein diets enriched with calcium, vitamin D, antioxidants and omega-3 proved effective in maintaining the health of astronauts. Furthermore, when the diet did not meet the Recommended Daily Intake (RDI), nutritional supplementation was essential to preserve bone density, physical performance, immunity, intestinal microbiota and eye health.